Tracking the infection dynamics of Fusarium oxysporum in Codonopsis pilosula based on GFP labelling - Shi, Mingming; Li, Huixia; Guo, Wei; Luo, Ning; Chen, Jinghuan; Liu, Yonggang; Liu, Rui; Mao, Zhenchuan (Frontiers in Plant Science, 2025)
IntroductionCodonopsis pilosula root rot, caused by Fusarium oxysporum, has caused severe damage to the C. pilosula industry. Due to the unclear pathogenic mechanisms of F. oxysporum on C. pilosula, the effective implementation of control measures has been greatly restricted.MethodsAn efficient protoplast preparation and genetic transformation system was established for F. oxysporum FO-1, enabling real-time tracking of fungal colonization in C. pilosula. Single-factor experiments were conducted to determine optimal conditions, followed by response surface methodology to further optimize enzymatic parameters. PEG-mediated transformation was performed to generate GFP-tagged strains for infection tracking.ResultsSingle-factor experiments identified the optimal conditions as 12-hour-old mycelia treated with 0.7 M NaCl and 20 mg/mL driselase at 28°C and 180 rpm for 4 h. Response surface methodology optimized parameters to 188.24 rpm, 4.51 h, and 27.5°C, yielding 1.44 × 108 CFU/mL protoplasts, representing a 30-fold improvement over single-factor optimization. PEG-mediated transformation produced 11 GFP-tagged strains, with FO-GFP-7 retaining wild-type morphology, growth rate, and pathogenicity. Microscopic observation revealed infection dynamics: conidia aggregated at the rhizome by 2 days post-inoculation (dpi), followed by phloem colonization at 4 dpi and vascular invasion at 6 dpi. Wound inoculation at the rhizome accelerated infection, consistent with field disease patterns linked to soil microfauna-induced injuries.DiscussionThis study provides a robust platform for investigating F. oxysporum pathogenicity in C. pilosula and offers guidance on protective measures to maintain rhizome integrity during cultivation.